How PrEP users constitute a community in the MSM population through their specific experience and management of stigmatization. The example of the French ANRS-PREVENIR study. Issue 2 (13th May 2020) - Puppo, C.; Spire, B.; Morel, S.; Génin, M.; Béniguel, L.; Costagliola, D.; Ghosn, J.; Mabire, X.; Molina, J. M.; Rojas Castro, D.; Préau, M.
ABSTRACT: The ANRS-PREVENIR (2017–2020) prospective cohort study aims to reduce the number of new HIV infections in the "Ile-de-France" region in France, by enrolling individuals at high risk of HIV infection and proposing daily and on-demand pre-exposure prophylaxis (PrEP). The qualitative component of the ANRS-PREVENIR study aimed to investigate social and relational evolutions associated with PrEP use in men who have sex with men (MSM). In 2018, 12 focus groups with MSM ( n  = 68) were conducted by a social sciences researcher in Paris. A thematic analysis was performed. Results showed that stigma concerning PrEP use is a complex issue, with various kinds of stigmatization being practiced, sometimes even by the wider MSM population and PrEP users themselves. All types of stigma identified were expressed in forms of verbal abuse which made PrEP use taboo. Inside the wider MSM population a PrEP-user "community" was identified which shared a certain complicity in terms of values and a positive attitude towards PrEP. The emergence of new intragroup and intergroup social norms should be taken into account by policy makers to promote a more positive image of PrEP users.